The complete mitochondrial genome of Paranemachilus genilepis (Zhu 1983) (Cypriniformes: Nemacheilidae) and its phylogenetic status - Luo, Congqiang (Mitochondrial DNA B Resour, 2020)
Paranemachilus genilepis (Zhu 1983) is a small and benthic loach species that mainly distributes in the Guangxi Province, China. To date, little was known about the genetic information of this species as no molecular sequence has been published. In this study, the complete mitochondrial genome of P. genilepis was reported using the Illumina MiSeq platform. The genome was 16,563 base pairs (bp) in length and its structure was identical to most genomes of bony fishes. Phylogenetic analyses supported two clades (I and II) among Nemacheilidae species and P. genilepis was sister to Oreonectes furcocaudalis.